Assessing the agroecological performance and sustainability of Community Supported Agriculture farms in Flanders, Belgium - Savels, Ruben; Dessein, Joost; Lucantoni, Dario; Speelman, Stijn (Frontiers in Sustainable Food Systems, 2024)
Agroecology is receiving increasing attention and recognition as a concept for transitions to more sustainable agricultural and food systems. There is however a lack of characterization of agroecology in agricultural and food systems, while integrated and holistic measurements of their sustainability are scarce. Community Supported Agriculture (CSA) is considered to be a system explicitly based on agroecological principles and practices which shows potential in the face of the sustainability challenges in agriculture and food systems, but its link with agroecology and its holistic sustainability performance have remained understudied. Therefore, we applied the Tool for Agroecology Performance Evaluation (TAPE) to 24 Community Supported Agriculture farms in the Flanders region of Belgium in order to characterize agroecology and to assess their multidimensional sustainability performance. Our results show that Community Supported Agriculture farms can be characterized as advanced agroecological systems, highlighted by their high to very high performance on many of the elements of agroecology. Moreover, our results show positive outcomes on several sustainability criteria across environmental, social and economic dimensions such as soil health, presence of natural vegetation and pollinators and ecological management of pests and diseases, as well as dietary diversity and profitability criteria like gross value, added value and net revenue. The integration and role of animals in these agroecosystems and the importance of - and dependence on - labor are however identified as two critical aspects regarding the agroecological transitions and sustainability of Community Supported Agriculture. Our findings emphasize the exemplary role Community Supported Agriculture could play in broader agroecological transitions, which, coupled with their high performance on several sustainability criteria, highlight the potential contribution of Community Supported Agriculture, and by extension of agroecology itself, to more sustainable agricultural and food systems in Flanders and beyond.